2000
DOI: 10.1034/j.1600-0447.2000.102004276.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom profiles of gender dysphoric patients of transsexual type compared to patients with personality disorders and healthy adults

Abstract: TS patients selected for sex reassignment showed a relatively low level of self-rated psychopathology before and after treatment. This finding casts doubt on the view that transsexualism is a severe mental disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
4
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 10 publications
(12 reference statements)
9
101
4
4
Order By: Relevance
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…High percentages of psychiatric comorbidity, however, are not always found. In many studies, transsexuals were found to generally function well psychologically in the nonclinical range (e.g., Cole, O'Boyle, Emory, & Meyer, 1997;Gómez-Gil, Trilla, Salamero, Godás, & Valdés, 2009;Haraldsen & Dahl, 2000;Mate-Kole, Freschi, & Robin, 1990;Miach, Berah, Butcher, & Rouse, 2000;Seikowski, Gollek, Harth, & Reinhardt, 2008;Smith, van Goozen, & CohenKettenis, 2001;Smith et al, 2005). Indeed, clinically, one may see applicants who are employed, have relationships, and function socially without any problems, yet very strongly desire sex reassignment.…”
Section: The Necessity Of the D Criterion For A Gid Diagnosismentioning
confidence: 99%
“…Se ha constatado en diversos estudios (Haraldsen y Dahl, 2000;Cano y Bergero, 2003), a que las personas transexuales que tienen la posibilidad de realizar los tratamientos de reasignación sexual y que son apoyados emocionalmente por la familia, especialmente por la madre, muestran un nivel bajo de conductas de riesgo y de síntomas psicopatológi-cos, tanto antes como después del tratamiento. En cambio, los padres que reaccionan de forma culpabilizadora, aumentan la vulnerabilidad, que ya de por sí padecen debido a su condición, aumentando la posibilidad de que aparezcan episodios depresivos e intentos de suicidio (Aguado, Ruíz y Mas, 2001).…”
Section: Consecuencias Psicosociales Conductas De Riesgo Y Agresioneunclassified
“…25,26 As far as psychopathology is concerned, the results are mixed: whereas some studies have reported higher prevalence of Axis I and II Disorders, 27,28 others found no differences in the level of psychopathology between GID subjects and controls. [29][30][31][32] Only one study has focused on the prevalence of CM in male-to-female (MtF) GID subjects, reporting a higher prevalence of emotional abuse and neglect in comparison with psychiatric inpatients. 33 Accordingly, a previous research performed on a sample of self-defined female-to-male transsexuals found a 60% prevalence of severe child abuse.…”
Section: Introductionmentioning
confidence: 99%